THE APPLICATION OF THE DOUBLE LOOP PROBLEM SOLVING (DLPS) MODEL TO IMPROVE STUDENT LEARNING OUTCOME OF MATRIX MATERIALS IN CLASS XI MM 2 SMK NEGERI 1 DLANGGU - Kinaah (Jurnal Scientia, 2022)
This study aims to determine student learning outcomes on matrix material through the application of the Double Loop Problem Solving (DLPS) learning model at SMK Negeri 1 Dlanggu Mojokerto class XI MM 2 semester 1 of the 2019/2020 school year. This research is classroom action research (CAR) which was carried out at SMK Negeri 1 Dlanggu Mojokerto class XI MM 2 semester 1 of the 2019/2020 school year, from August to October 2019. The research was carried out through 2 cycles with each cycle consisting of planning, implementation, observation and reflection. Based on the results of research and discussion, it can be concluded that the application of the double loop problem solving learning model can improve student learning outcomes. This can be seen from the increase in mastery learning outcomes from the first cycle to 86.11% then increased in the second cycle to 91.66%. In addition, the application of the double loop problem solving learning model in class XI MM 2 SMK Negeri 1 Dlanggu in semester 1 of the 2019/2020 academic year in Physical Education lessons with the main matrix material can increase student activity, implementation of lesson plans and student scientific behavior. And the average student learning outcomes also increased rapidly from the first cycle of 81.12 increased to 86 in the second cycle.